2016
DOI: 10.1142/s0217984916501967
|View full text |Cite
|
Sign up to set email alerts
|

Analytic study of heat transfer with variable viscosity on solid particle motion in dusty Jeffery fluid

Abstract: In this paper, effects of variable viscosity with heat transfer on solid particle motion of dusty Jeffrey fluid model through a planar channel has been examined. The governing flow problem for fluid phase and dusty phase is formulated with the help of momentum and energy equation. The resulting coupled ordinary differential equations have been solved analytically and closed form solutions are presented. The influence of all the physical parameters are sketched for velocity profile, pressure rise and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…According to the best of author's knowledge, no such attempt has been made on solid particle-fluid of dusty MHD Ree-Eyring fluid under the effects of heat transfer. Some more pertinent studies on particlefluid with peristaltic flow can found in [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…According to the best of author's knowledge, no such attempt has been made on solid particle-fluid of dusty MHD Ree-Eyring fluid under the effects of heat transfer. Some more pertinent studies on particlefluid with peristaltic flow can found in [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Ellahi et al [13] examined the combined effects of heat and mass transfer on peristaltic motion of viscous fluid through a non-uniform rectangular duct. Few more data on the current theory are available in [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Jha and Gwandu [16] extended the work of Wang and Ng [15] by considering electrically conducting fluid in the presence of transverse magnetic field. Bhatti and Zeeshan [17] analysed the hydrodynamics and heat transfer of dust-particle-containing fluid with variable viscosity in a rectangular horizontal channel. Their major findings include: (1) the velocity profile diminishes as a result of the influence of particle volume fraction (2) the temperature profile is a decreasing function of volume fraction.…”
Section: Introductionmentioning
confidence: 99%